Peran Product Knowledge dalam Memediasi Pengaruh Social Media Influencer Terhadap Purchase Intention pada Produk Honda Electric Moped One - Ni Nengah Akina; Ni Kadek Suryani; Inten Pertiwi (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2025)
Background: Purchase intention is often driven by consumers’ emotional responses and their knowledge about a product—both of which can be significantly shaped by social media influencers. These influencers play a key role in disseminating product information and generating consumer interest. Objective: This study aims to reevaluate the mediating role of product knowledge in the relationship between social media influencers and consumers’ intention to purchase, particularly in the context of electric vehicle promotion. Methods: The study employed a non-probability purposive sampling technique to survey 120 respondents residing in Bali, all of whom possess a valid driver’s license and follow Astra Honda Motor (AHM) Bali social media influencers. Data were collected through structured questionnaires and analyzed using path analysis to assess both direct and mediated relationships among variables. This approach was chosen for its effectiveness in modeling complex relationships and testing mediation effects. The data were analyzed using mediation analysis with SPSS Macro Process Model 4 by Hayes. Results: Social media influencers have a significant direct impact on both product knowledge and purchase intention (p < 0.01). Product knowledge also shows a significant direct effect on purchase intention (p = 0.0254). Moreover, product knowledge plays a significant mediating role in the relationship between social media influencers and purchase intention (CI: 0.3028-0.8213). Conclusion: The findings underscore that social media influencers not only directly influence consumer purchase intentions but also do so indirectly by enhancing product knowledge. This highlights their strategic importance in boosting consumer awareness and engagement